Elevated CO2 (free-air CO2 enrichment) increases grain yield of aluminium-resistant but not aluminium-sensitive wheat (Triticum aestivum) grown in an acid soil. (14th September 2018) - Dong, Jinlong; Grylls, Stephen; Hunt, James; Armstrong, Roger; Delhaize, Emmanuel; Tang, Caixian
Abstract: Background and Aims: Soil acidity currently limits root growth and crop production in many regions, and climate change is leading to uncertainties regarding future food supply. However, it is unknown how elevated CO2 (eCO2 ) affects the performance of wheat crops in acid soils under field conditions. We investigated the effects of eCO2 on plant growth and yield of three pairs of near-isogenic hexaploid wheat lines differing in alleles of aluminium-resistant genes TaALMT1 (conferring root malate efflux) and TaMATE1B (conferring citrate efflux). Methods: Plants were grown until maturity in an acid soil under ambient CO2 (aCO2 ; 400 µmol mol −1 ) and eCO2 (550 µmol mol −1 ) in a soil free-air CO2 enrichment facility (SoilFACE). Growth parameters and grain yields were measured. Key Results: Elevated CO2 increased grain yield of lines carrying TaMATE1B by 22 % and lines carrying only TaALMT1 by 31 %, but did not increase the grain yield of Al 3+ -sensitive lines. Although eCO2 promoted tiller formation, coarse root length and root biomass of lines carrying TaMATE1B, it did not affect ear number, and it therefore limited yield potential. By contrast, eCO2 decreased or did not change these parameters for lines carrying only TaALMT1, and enhanced biomass allocation to grains thereby resulting in increased grain yield. Despite TaMATE1B being less effective than TaALMT1 at conferring Al 3+ resistance based on root growth, the gene promoted grain yield to a similar level to TaALMT1 when the plants were grown in acid soil. Furthermore, TaALMT1 and TaMATE1B were not additive in their effects. Conclusions: As atmospheric CO2 increases, it is critical that both Al 3+ -resistance genes (particularly TaALMT1 ) should be maintained in hexaploid wheat germplasm in order for yield increases from CO2 fertilization to be realized in acid soils.